Dynamic buckling-driven delamination of thin films. (September 2022) - Malkiel, N.; Rabinovitch, O.
Graphical abstract: Highlights: The dynamics of buckling-driven delamination of thin film on substrate is first studied. The novelty is in the consideration of the dynamics of the buckling driven delamination mechanism. A nonlinear dynamic 1D FE model is developed and loaded by thermally induced stresses. The model integrates geometrically nonlinear BE beam and cohesive interface approach. Unstable buckling-delamination processes are detected, resulting dynamic effects are explored. Abstract: This paper studies the dynamic buckling-driven delamination of thin films. A 1D case of an initial delamination in a thin film bonded to a rigid substrate through a cohesive interface and subjected to thermally-induced stresses is investigated. Emphasis is placed on the dynamic nature of the compressive delamination process. For that purpose, a 1D problem and its weak form are formulated based on the cohesive interface approach, the well-established geometrically nonlinear Bernoulli-Euler beam model for the thin film, and Newtonian dynamics. Based on this formulation, the Finite Element numerical counterpart of the model is derived to analyze and capture the dynamic effects of the mutual and coupled dynamic evolution of the buckling and delamination nonlinear phenomena. The innovative aspects of the formulation are the consideration of the current problem in a dynamic framework and the consideration of the inertial forces. In that sense, it innovates by the combination of methodologies (cohesive interfaces, Bernoulli-Euler beam theory, geometrical nonlinearity, Newtonian dynamics) and by the application of the combined methodology to investigate a realistic problem that was not studied in this framework before. The model is used to examine the coupled nonlinear dynamic structural response. It shows that the mutual and coupled evolution of the buckling and delamination phenomena may lead to a simultaneous and unstable evolution of the two, which results in significant dynamic effects. A detailed comparison of the dynamic results with a reference static solution highlights the role played by the inertial forces and the time scales associated with the dynamic instability. The buckling-driven delamination then evokes a significant time dependent evolution of displacements, energies, delamination length, reactions, and internal forces. The sensitivity to changes in the parameters defining the problem is also demonstrated. The novelty of this paper is the consideration of the Newtonian dynamics in the problem of buckling-driven delamination of thin film systems and the investigation and description of their significant dynamic effects on the structural response. This study establishes and demonstrates the significance of the dynamic aspects of the buckling-driven delamination process in thin film systems.